ORGANIZOWANIE MILICJI OBYWATELSKIEJ NA ZIEMI LUBUSKIEJ (MARZEC- LIPIEC 1945 R.) - Piotr Krystians (In Gremium. Studies in History, Culture and Politics, 2011)
THE ORGANIZATION OF CITIZENS' MILITIA UNITS IN ZIEMIA LUBUSKA (MARCH- JULY 1945)